Alternative Economic Policies for the Revitalization of U.S. Central Cities - Chandler, Cleveland A.; David, Wilfred L. (American Economic Review, 1979)
The formulation of suitable policies and strategies for improving the economic viability of U.S. central cities constitutes one of the most crucial tasks facing policymakers in the urban field. The problem has become increasingly severe for the large number of central cities in the North East, North Central, and Western states. The basic issue is one of determining the character, dimensions, and magnitudes of policies that will reverse the process of cumulative decay and propel urban core areas into a new orbit of self-sustaining development. This paper examines some structural dimensions relating to change in central cities, and how these can be influenced by means of concerted policy action. An underlying assumption is that most policies for urban change tend to produce limited results because they are anchored on unsuitable conceptual underpinnings. The paper therefore attempts to develop a systematic framework of analysis with a view to highlighting some of the major structural dimensions of the urban environment which are amenable to those kinds of policy interventions necessary for revitalization. The paper is divided into three parts. Section I briefly outlines the conceptual focus. This is illustrated by a simple policy model in Section II. The policy implications for central city revitalization are drawn in the final section. I. Conceptual Underpinnings